2015
DOI: 10.1080/1745039x.2015.1058619
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oil and beef tallow in dry extruded diets for adult dogs

Abstract: The aim of the study was to determine the effects of two different fat sources (soybean oil (SO) and beef tallow (BT)) in dry extruded dog diets on the intake of food and metabolizable energy (ME), on faecal characteristics and apparent total tract digestibility (ATTD) of nutrients and energy. Ten adult dogs of different breeds were used in a Latin square design. Five experimental diets were designed from a basal diet. A Control diet was coated with 1% SO and four other diets were obtained by coating the basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Epidemiological and experimental evidence suggest that dietary F:C ratio affects BW through energy surfeits facilitated by the high energy density of fat (Lissner and Heitmann 1995). Increasing dietary F:C ratio from 34:34 to 48:22 resulted in an increase in ADMI, which was expected and agrees with the data of Marx et al (2015) who studied that there was an increased in energy intake when dog fed high-fat diet. We speculate that the high F:C ratio diets is motivated by the correspondingly higher ME intake and, thereby, the higher BWs.…”
Section: Discussionsupporting
confidence: 87%
“…Epidemiological and experimental evidence suggest that dietary F:C ratio affects BW through energy surfeits facilitated by the high energy density of fat (Lissner and Heitmann 1995). Increasing dietary F:C ratio from 34:34 to 48:22 resulted in an increase in ADMI, which was expected and agrees with the data of Marx et al (2015) who studied that there was an increased in energy intake when dog fed high-fat diet. We speculate that the high F:C ratio diets is motivated by the correspondingly higher ME intake and, thereby, the higher BWs.…”
Section: Discussionsupporting
confidence: 87%
“…For comparison, choice white grease has an unsaturated:saturated ratio of 0.31, compared with beef tallow (0.08), poultry fat (0.71), and soybean oil (4.07; NRC, 2006). Diets containing higher amounts of unsaturated fats (i.e., soybean oil) have been demonstrated to have higher fat digestibility by dogs (Marx et al, 2015), which may have influenced the coefficients of AHF digestibility observed in the present study.…”
Section: Apparent Total Tract Macronutrient and Energy Digestibilitiesmentioning
confidence: 68%
“…Hyperbolic effect given by the equation: y = 98.5 − 13.62/x (R 2 = 0.72; SE = 1.1) F I G U R E 3 Fat digestibility (CTTAD, %) as a function of AHEE intake (g per kg BW per day) of puppies. Hyperbolic effect given by the equation: y = 99.1 − 26.13/x (R 2 = 0.613; SE = 1.30) Romsos, Hornshus, and Leveille (1978), Kendall, Holme, and Smith (1982), Marx et al (2015) and Marx et al (2017). Fat is a highly digestible energy source, and most fat sources included in dog and cat foods have CTTAD greater than 90.0%.…”
Section: Conflicting Results On Fat Digestibility In Dogs Of Differenmentioning
confidence: 99%
“…Although some studies on the digestibility of several fat sources for dogs and cats are published (Marx, Trevizan, & Ahlstrøm, 2015), there is little information on nutrient utilization in dogs younger than 1 year of age (Swanson, Kuzmuk, Schook, & Fahey, 2004) or on the digestibility of different nutrients for dogs of different ages (Taylor, Adams, & Neville, 1995; Weber, Martin, Biourge, Nguyen, & Dumon, 2003).…”
Section: Introductionmentioning
confidence: 99%